Handbook of research on human performance and instructional technology - Song, Holim; Kidd, Terry T. (Hershey, Pa. : Information Science Reference, 2010)
"This book addresses the connection between human performance and instructional technology with teaching and learning, offering innovative ideas for instructional technology applications and e-learning"--Provided by publisher.
Includes bibliographical references and index
Keywords: Educational technology; Performance technology; Web-based instruction; Instructional systems -- Design